Improving Fast and Effective Reading Skills Through Skimming and Scanning Strategies - Wulan Wahyu Kusuma; Inkha Aulia Jannyfer Nursyahputri; Adhelia Safirah; Rahma Evelyna Hardiana Putri; Laily Zakiyaturrahmah; Trinil Dwi Turistiani (The Future of Education Journal, 2026)
This study aims to examine the improvement of fast and effective reading skills through the application of skimming and scanning strategies. Fast and effective reading skills are important literacy competencies needed by students in facing the rapid development of information in the digital era. However, students’ reading abilities are still relatively low due to linear reading habits and the lack of appropriate reading strategies. This study employed a descriptive qualitative approach with students selected purposively as the research subjects. Data collection techniques included reading tests, reading comprehension tests, and observations. The data were analyzed descriptively to determine the relationship between reading speed and reading comprehension levels. The results showed that skimming and scanning strategies were able to improve students’ reading skills in terms of both speed and comprehension. The skimming technique helped students identify main ideas quickly, while scanning enabled them to find specific information effectively. In addition, the implementation of these strategies also supported the improvement of students’ concentration, accuracy, and critical thinking skills. Nevertheless, the implementation of these strategies still faces several obstacles, such as teachers’ limited understanding of speed-reading techniques, limited learning media, and students’ lack of vocabulary mastery. Therefore, a more structured and continuous implementation is needed so that skimming and scanning strategies can be optimized in reading instruction.